Analisis Kebutuhan Jumlah Tenaga Kerja Optimal Berdasarkan Penilaian Beban Kerja Fisik Menggunakan Cardiovascular Load dan Stopwatch Time Study (Studi Kasus UD. Batu Alam Kabupaten Aceh Barat) - Sofiyanurriyanti, Sofiyanurriyanti; Rahma, Cukri; Pandria, T. M Azis; Hardianto, Hardianto (Universitas Teuku Umar, 2021)
This study aims to identify complaints of musculoskletal disorders experienced by operators due to load imbalance received by workers using the Standard Nordic Quistionaire, determine the workload received by workers based on the cardiovascular load method in the paving block manufacturing process and determine the optimal number of workers. according to company needs. about making paving blocks. Based on the results of the SNQ questionnaire distribution, the highest complaints occurred at the work station mixing cement with sand in making paving blocks and at the station for lifting raw materials to the tub for the paving block molding process with a percentage of 80.36 categorized as quite heavy, the second highest percentage was at the transfer station for paving blocks. which is printed to the drying place and moving the paving block to the soaking place with a percentage of 79.46% is categorized as quite heavy and the smallest percentage is at the paving block printing workstation with a percentage of 57.14% categorized as heavy, to overcome this it is recommended to increase the number of workers for the workload and complaints experienced by operators related to the risk of spinal cord injury (musculoskeletal) due to multiple work (Multi Tacking). Workload received by workers based on the cardiovascular load method in the process of making paving blocks with a workload value of 38.92%, the second highest workload with a load value of 34.68% and the third highest workload, namely the Nizam operator with a workload value of 31.60 so that the number The proposed workforce must optimally be employed in accordance with the company's needs in making paving blocks, namely 2 workers with the previous number of workers being 3 workers where the workers also work concurrently in carrying out their work activities.